PENGARUH DUKUNGAN SOSIAL DAN KARIR EFIKASI DIRI TERHADAP PILIHAN KARIR DENGANEKSPLORASI KARIR SEBAGAI PEMEDIASI PADA MAHASISWA S1 FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS SYIAH KUALA - Eka Putri Sara; Sofyan Idris (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2020)
This study aims to determine the effect of social support and career self-efficacy on career choices with career exploration as a mediator in undergraduate students at the Faculty of Economics and Business at Syiah Kuala University. The sample in this study was 240 students from the Faculty of Economics and Business at Syiah Kuala University. Data collection equipment used in this study was a questionnaire. The sampling method used is probability sampling stratified random sampling. Hierarchical Linear Modeling (HLM) is used as an analytical method to determine the effect of all the variables involved.Based on the results of the HLM analysis, research shows that Social Support has a positive effect on Career Options, Career Self-Efficacy has a positive effect on Career Options, Social Support has a positive effect on Career Exploration, Career Self-Efficacy has a positive effect on Career Exploration, Career Exploration has a positive effect on Career Options, Career Exploration mediates Social Support for Career Options in full, and Career Exploration partially mediates Career Self-Efficacy of Career Options.